Autonomously Self‐Reporting Hard Coatings: Tracking the Temporal Oxidation Behavior of TiN by In Situ Sheet Resistance Measurements. (12th February 2020) - Stelzer, Bastian; Momma, Markus; Schneider, Jochen M.
Abstract: Monitoring the structural health and integrity of coated components is of vital importance to increase their lifetime and the overall sustainability of the targeted applications. Here, the temporal oxidation behavior of TiN thin films is tracked using in situ sheet resistance measurements. Based on correlative film morphology, structure, and local composition data, it is evident that observed resistance changes are caused by oxidation of TiN. Thickness measurements of the remaining TiN under the oxide layer are in very good agreement with thicknesses deduced from in situ sheet resistance measurements. Hence, the in situ measured sheet resistance is an autonomous self‐reporting property useful for tracking the temporal oxidation behavior of TiN coatings. Abstract : The temporal oxidation behavior of TiN thin films is tracked via in situ resistance measurements. Thickness measurements of the remaining TiN under the oxide layer are in very good agreement with thicknesses deduced from in situ resistance measurements. Hence, electrical resistance is an autonomous self‐reporting property for tracking the oxidation behavior of TiN coatings.